KEWENANGAN ANGGOTA DPRD DALAM PENGAWASAN TERHADAP PELAKSANAAN PEMBANGUNAN DAERAH DI KABUPATEN SINJAI PERSPEKTIF SIYASAH SYAR'IYYAH - Yaumil Khaeriyah,; Jafar, Usman; Ishak, Nurfaika (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
This study aims to determine the implementation of the supervision of DPRD members on the implementation of regional development in Sinjai Regency, the supporting and inhibiting factors of DPRD in supervising the implementation of regional development in Sinjai Regency, and the concept of DPRD in supervising the implementation of regional development in the Siyasah Syar'iyyah perspective. This research is a field research (Field Research) using a juridical and syar'i approach. The source of the data is primary data. The data were collected by conducting field research conducted in Sinjai Regency by means of observation, interviews, documentation and reference searches. Furthermore, data processing and analysis went through three stages, namely; data reduction, data presentation, and conclusion drawing. The results showed that: The implementation of supervision of DPRD members on the implementation of regional development in Kab. Sinjai is adjusted to Law Number 23 of 2014 concerning Regional Government. Supporting factors in the supervision of DPRD members include the existence of financial assistance from the central and district governments, being aware of the functions and responsibilities in accordance with the law, planning and conducting recesses while the inhibiting factors in supervising DPRD members include difficult-to-reach areas, human resources, and there are still many programs resulting from the musrenbang in the village that have not been accommodated until now. The concept of DPRD in carrying out supervision according to Siyasah Syar'iyyah must be based on the Qur'an and Hadith for the benefit of humans.